Predicting the dental implant stability based on the antiresonance phase of a piezo-based impedance sensor - Paramita Banerjee; Abhijit Chakraborty; Ratna Ghosh; Bhaswati Goswami (Wolters Kluwer Medknow Publications, 2017)
Background: The stability of dental implants (DIs) in in vivo tests can be determined using noninvasive resonance frequency analysis technique. A low-cost piezo-based sensor has been developed for this purpose which uses a readily available two-terminal piezo element, to which a metal substrate is adhesively glued for attaching the implant. Aim: The attainment of implant stability in dynamic tests using this sensor must be standardized in terms of the major antiresonance (AR) in the impedance phase responses using sensor-DI assembly. This will be used to predetermine the dimensions of the glued metal substrate in the sensor design. Materials and Methods: Multiple sensors with varying sensor dimensions were developed. Static and dynamic impedance studies were performed on these and corresponding sensor-implant assemblies. Static tests as well as in vitro tests with the sensor-implant assembly dipped in a standardized dental plaster mixture were performed in controlled laboratory conditions. Results: The probability of acceptance of the hypothesis has been checked using binomial distribution with a significance level of 5%. Statistically observed that for 95% of the cases where the DI becomes stable in dental plaster, both AR phase and AR frequency (ARF) return to their corresponding static values. Furthermore, for a piezo element, whose ARF is within 6-6.6 kHz, the sensor yields maximal phase when the length of the metallic strip is 2 cm. Conclusions: Experimental validation supports both claims. Hence, this work can be extended to in vivo DI stability determination and design aspects of the corresponding sensor.